Determinants of SME Financial Performance in the Digital Transformation Era: The Role of Accounting Digitalization, Accounting Information Systems, and Financial Applications - Andi Riska Andreani; Amiruddin Yunus; Asri Usman; Wahyuni Saleh; Syafaruddin Syafaruddin (International Journal of Economics, Management and Accounting, 2026)
Digital transformation has fundamentally altered the financial management landscape for Micro, Small, and Medium Enterprises (SMEs) in Indonesia. However, there remains an empirical gap regarding how significantly accounting digitalization, accounting information systems (AIS), and digital financial applications jointly affect SME financial performance, particularly in Makassar City. This study analyzes the effects of accounting digitalization (X₁), accounting information systems (X₂), and financial application/website usage (X₃) on SME financial performance (Y), both partially and simultaneously. A quantitative cross-sectional survey approach was employed with 120 respondents selected using purposive sampling among SMEs in Makassar City that had adopted at least one digital financial management tool. Data were analyzed through validity and reliability tests, classical assumption tests, multiple linear regression, F-test, t-test, and coefficient of determination using IBM SPSS Statistics 26. The F-test revealed that the three independent variables simultaneously and significantly affect SME financial performance (F = 61.847; sig. = 0.000). Partially, accounting digitalization (β = 0.358; t = 3.931; sig. = 0.000), accounting information systems (β = 0.283; t = 3.053; sig. = 0.003), and financial application/website usage (β = 0.239; t = 2.852; sig. = 0.005) each positively and significantly affect SME financial performance. The coefficient of determination (R² = 0.615) indicates the three variables explain 61.5% of SME financial performance variation. Accounting digitalization is the strongest predictor of SME financial performance, followed by AIS and financial application usage. Policy implications include the urgency of digital accounting literacy training and technology infrastructure support for SME owners.